Sight Enhancement Services - A Safety Net or a Spider's Web? - Herie, E.J; Grace, G (Canadian Journal of Optometry, 2021)
This paper will review the development of the "human services'' aspect of sight enhancement, and the integral role of human services in an effective and comprehensive sight enhancement system.